2012
DOI: 10.1108/10610421211264900
|View full text |Cite
|
Sign up to set email alerts
|

Brand mergers: examining consumers' responses to name and logo design

Abstract: PurposeIn the context of a merger, the management of corporate identity – in particular of corporate names and logos – assumes a critical role. This paper aims to explore how name and logo design characteristics, and specifically figurativeness, influence consumer preferences in the context of a brand merger, in the banking sector.Design/methodology/approachThis study develops a typology of the alternative corporate identity structures that may be assumed in the context of a brand merger by drawing on a litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 58 publications
0
31
0
1
Order By: Relevance
“…Jin et al (2015) found that the association of a famous brand name with a dissimilar product category led to a worse acceptance than the strategy of new brand creation. However, in addition to this brand name extension strategy, brand logo extension is another important extension strategy because a brand can be identified by its brand logo as well as its brand name (Fombrun and Van Riel, 1997; Klink, 2003; Guzmán et al, 2012). In this study, the brand name is written in Chinese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jin et al (2015) found that the association of a famous brand name with a dissimilar product category led to a worse acceptance than the strategy of new brand creation. However, in addition to this brand name extension strategy, brand logo extension is another important extension strategy because a brand can be identified by its brand logo as well as its brand name (Fombrun and Van Riel, 1997; Klink, 2003; Guzmán et al, 2012). In this study, the brand name is written in Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al (2014b) suggested that a two-stage categorization process (early low-level and similarity-based processing and late analytic and category-based processing) was involved in the evaluation process of perceived fit between the names of the parent brands and the extension products (Ma et al, 2014b). However, a parent brand can primarily be identified by not only its brand name but also its brand logo (Fombrun and Van Riel, 1997; Klink, 2003; Guzmán et al, 2012). Although brand extension appears to have two important extension strategies (brand name extension and brand logo extension), few studies concerning the strategy of brand logo extension have been performed to date.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in the brand literature have investigated the visual elements of logos, such as identifying the concepts of naturalness, harmony, elaborateness, parallelism, repetition, proportion and shape (Henderson and Cote, 1998). The figurative design of brand logos can create brand recall and recognition (Machado et al , 2012). Natural logo designs generate brand recognition and positive affect towards brands (Machado et al , 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Mas essa negociação pode ser muito desafiadora. Os públicos não proprietários da marca podem imaginar soluções identitárias muito mais ricas do ponto de vista afetivo (MACHADO et al, 2012a), nomeadamente privilegiando soluções não abstratas (SCHECHTER, 1993), "figurativas" (LENCASTRE, 1997;MACHADO et al, 2012b) e "naturalistas" COTE, 1998;MACHADO et al, 2015) que permitem narrativas. Neste caso, trata-se de um sinal cujo paradoxo (a árvore que não é verde) gera um significado enriquecido (a árvore é azul porque gera a água).…”
Section: Discussionunclassified